Comparative study of seroprevalence of toxoplasmosis between local workers and migrant workers in Malaysia - Eugene, Chan Boon Tek; Nimir, Amal Rashad; Isa, Noor Hayati Mohd; Hideto, Kino; Nordin, Anisah; Moktar, Norhayati (Archives of Medical Science, 2009)
Introduction: It is known that toxoplasmosis primary infection is usually subclinical, but in severely immunocompromised patients it may be life-threatening. To monitor the situations related to non-notifiable diseases among foreign arrivals to Malaysia, a survey on toxoplasmosis was undertaken. Material and methods: A serological study to determine Toxoplasma gondii IgG and IgM antibodies among 501 migrant males and 198 local male workers was conducted in a plantation and a detention camp in Selangor, Malaysia using subjects’ venous blood samples for serological study and subjects’ study sheet for demographic data collection. Results: The age of studied samples ranged from 19 to 45 years (geometric mean 29.9). The highest prevalence rate of 46.2% is demonstrated among Nepalese workers. Statistical analysis indicated that the IgG positive rate of the local residents was significantly higher than that of the migrants studied in this survey (p 0.05). No significant difference in the prevalence rates was noted among the migrants or local workers when they were grouped according to agricultural and non-agricultural occupations (p > 0.05). Conclusions: The continuous introduction of these infections may, in the long term, influence the epidemiology and further compromise the efforts in control and prevention. It is therefore pertinent to monitor the situations related to non-notifiable diseases.